Prospecção de óleos essenciais para controle de Musca domestica L. (Diptera: Muscidae) - Serafim, Ariane Julia (2022)
Musca domestica is a synanthropic insect, which in addition to causing disturbances to animals and humans; it is consider an important vector of diseases. The objective of the present work was to evaluate the toxicity of essential oils from Cinnamomum cassia and Cinnamomum camphora var. linalooliferum (lauraceous) on third instar larvae, pupae and adults of M. domestica and evaluate the preference of essential oils in adults. In the essential oils of C. cassia and C.camphora var. linalooliferum it founded as major compounds cinnamaldehyde <E> and linalool. Essential oils was solubilized in DMSO + sugar water at concentrations of 75.8 μl/ml for C. cassia 53.39 μl/ml for C. camphora var. linalooliferum, which correspond to the LD50 for housefly pupae. For larvae and pupae, 50 third-instar larvae and 50 pupae were used for each oil dose (LD25, LD50 and LD90) obtained in previous tests. The essential oils has been solubilized in DMSO, water + sugar and the control consisted of DMSO, water and sugar, applying 1μl of the essential oil solution on the back of each third-instar larva and each pupa. Mortality and reproduction of adults formed from treated larvae and pupae it verified. C. cassia oil was more toxic to housefly larvae, pupae and adults. Oils from Cinnamomum cassia reduced the amount of viable adult eggs from treated larvae and pupae. C. camphora var. linalooliferum reduced the pre-oviposition period and the total number of eggs laid by adults from third-instar larvae. The duration of the larval period, it reduced in the LD25 and LD50 treatments of C. cassia and C. camphora var. linalooliferum. Housefly adults showed a greater preference for the essential oils of C. camphora var. linalooliferum and Cinnamomum cassia showed greater repellency for adults. Essential oils from C. cassia and C. camphora var. linalooliferum have potential for use in M. domestica management programs, since they were toxic to this insect pest.